2009
DOI: 10.1603/029.102.0156
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leaf Sheath Lignification and Anatomy in Resistance Against Southern Chinch Bug (Hemiptera: Blissidae) in St. Augustinegrass

Abstract: Southern chinch bug, Blissus insularis Barber (Hemiptera: Blissidae), is the most serious insect pest of St. Augustinegrass Stenotaphrum secundatum (Walter) Kuntze, a common lawngrass grown in southeastern U.S. states. Host plant resistance to southern chinch bug has been identified in the polyploid St. Augustinegrass 'FX-10' and the diploid 'Captiva'. The objective of this research was to identify possible physical mechanism(s) explaining chinch bug resistance in these cultivars. We studied the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
(37 reference statements)
0
28
0
Order By: Relevance
“…Although chinch bugs make salivary sheaths, sometimes quite elaborate ones (Anderson et al 2006, Rangasamy et al 2009), they do so through the tightly wrapped immature leaf sheaths in grass blades. Thus, each salivary sheath traverses multiple young leaves separated by layers of air space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chinch bugs make salivary sheaths, sometimes quite elaborate ones (Anderson et al 2006, Rangasamy et al 2009), they do so through the tightly wrapped immature leaf sheaths in grass blades. Thus, each salivary sheath traverses multiple young leaves separated by layers of air space.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary sheaths of western and southern chinch bug are frequently branched as they move through the leaf tissue (Anderson et al 2006, Rangasamy et al 2009), and in the case of the western chinch bug, terminate primarily in the vascular tissue (Anderson et al 2006). The target tissue of southern chinch bug stylets has not been deÞnitively identiÞed; however, stylets routinely pass through up to Þve leaf sheaths as the insects attempt to reach the youngest meristematic tissue within a leaf shoot (Rangasamy et al 2009). …”
mentioning
confidence: 99%
“…These findings indicate that the host plant may serve as a direct source of gut symbiont Burkholderia for B . insularis that feed by piercing through the innermost leaf sheath [14]. Plant-to-insect transmission is supported also by the rearing experiment using live St. Augustinegrass plants, showing that survivorship of B .…”
Section: Discussionmentioning
confidence: 99%
“…The Southern chinch bug, Blissus insularis Barber (Hemiptera: Lygaeoidea: Blissidae), is a plant-phloem-feeding pest of St. Augustinegrass, Stenotaphrum secundatum (Walter) Kuntze [13,14]. This chinch bug harbors a high density of exocellular Burkholderia within its tubular midgut crypts [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…1), in the Southern chinch bug, Blissus insularis Barber (Hemiptera: Lygaeoidea: Blissidae) (12). This insect, a primary pest of St. Augustinegrass, Stenotaphrum secundatum (Walter) Kuntze (20,21), feeds on the grass phloem, resulting in diminished grass growth, yellowing and brown blade color, and the eventual death of grass patches (22,23). Investigations of multiple B. insularis field populations demonstrated that complex Burkholderia ribotypes were present within and among the populations (12).…”
mentioning
confidence: 99%